ANALISIS SRATEGI PEMASARAN GUNA PENGEMBANGAN USAHA UMKM KERUPUK MERAH JATI DENGAN MENGGUNAKAN SWOT - Deri Kurniadi; Aan Rahmadi (Jurnal Teknik Industri Terintegrasi, 2021)
AbstractRed Jati crackers UMKM as a producer that produces red crackers. Reliable strength. Red Jati crackers have an advantage in terms of price, but need improvements in terms of packaging made as attractive as possible so that consumers are more interested and add to the selling value. The weaknesses that are owned by Red Jati Crackers are: first, they do not have a typical company so that the company will experience a financial crisis (decline) if the company is affected by the dropping or falling world economy and secondly does not use promotional or advertising services, both visual and non-visual. The biggest opportunity that Red Jati Crackers can get is to dominate the monopolistic market. The biggest threat faced by Red Jati Crackers is the purchasing power of consumers. SWOT analysis of IFAS (Intermal Factors Analysis Summary) material factors Total score of 2.32 Strength (Strength) while Weakness (Weakness) total score of 0.76. The total score is all 3.08. EFAS External Factors (External Factors Analysis Summary) Opportunities total score of 2.14 while Threat (Threat) total score of 0.45. The total score is 2.59 in all. Red Jati crackers are in a development position (Growth) with the SO (S) Strategy to increase Strength (O) to achieve the goal. Keywords: SWOT, Strengths, Weaknesses, Opportunities, Threats, Marketing Strategy, SWOT Matrik.